Rudolf von Laban's Labanotation: the origin of notational analysis methods in sport sciences. [La Labanotación de Rudolf von Laban: el origen de los métodos de análisis notacional en las ciencias del deporte]. - Miguel Ángel Gómez (Ramón Cantó Alcaraz, 2015)
Rudolf von Laban (born in 1879, Poszony, Hungary; and died in 1958, Addlestone, England) was one of the most significant figures in the movement analysis and dance in Europe during the 20th century (Lepczyk, 2009). He was considered a pioneer of modern dance and a theorist of the dance movements. Particularly, his work was considered a breakthrough in the history of dance notation systems (Barbacci, 2002; Lepczyk, 2009, 2011). According to Barbacci (2002) Laban had a live marked by idealism and deep disillusions, on the one hand, he lived in the most important cultural cities in Europe (Paris, Vienna, Munich, Berlin, Zurich, and London) where he met and kept contact with intellectuals and artists, this experience allowed him to be influenced by some theories such as "Naturphilosophie", which developed a biological and romantic vision of movements. In fact, Laban considered the movement as a "Dance of Nature" (Barbacci, 2002). On the other hand, he also was influenced by negative disillusions because he lived through two World Wars, the Weimar Republic and also the origins of Nazism. Laban tried to study the movement from a natural perspective where man has a place in the universe, thus the movement is related to the mind and body, as well as to individuals and groups (Barbacci, 2002). (Full text/texto completo).